Data feminism - D'Ignazio, Catherine; Klein, Lauren F. (The MIT Press, 2020)
"A new way of thinking about data science and data ethics that is informed by the ideas of intersectional feminism. Today, data science is a form of power. It has been used to expose injustice, improve health outcomes, and topple governments. But it has also been used to discriminate, police, and surveil. This potential for good, on the one hand, and harm, on the other, makes it essential to ask: Data science by whom? Data science for whom? Data science with whose interests in mind? The narratives around big data and data science are overwhelmingly white, male, and techno-heroic. In Data Feminism, Catherine D'Ignazio and Lauren Klein present a new way of thinking about data science and data ethics–one that is informed by intersectional feminist thought. Illustrating data feminism in action, D'Ignazio and Klein show how challenges to the male/female binary can help challenge other hierarchical (and empirically wrong) classification systems. They explain how, for example, an understanding of emotion can expand our ideas about effective data visualization, and how the concept of invisible labor can expose the significant human efforts required by our automated systems. And they show why the data never, ever 'speak for themselves.' Data Feminism offers strategies for data scientists seeking to learn how feminism can help them work toward justice, and for feminists who want to focus their efforts on the growing field of data science. But Data Feminism is about much more than gender. It is about power, about who has it and who doesn't, and about how those differentials of power can be challenged and changed."-
Keywords: approches et analyses; discipline; données scientifiques; histoire et politique; intersectionnalité; patriarcat; privilèges; projet charge mentale; pédagogie; racisme; rapports de pouvoir; ressource en ligne; sciences; sciences humaines; systèmes d'oppressions; thématiques; travail; travail scientifique; épistémologie

Save Yourself - Esposito, Cameron (Grand Central Publishing, 2020)
This "hilarious and honest" bestselling memoir from a rising comedy star tackles issues of gender, sexuality, feminism, and the Catholic childhood that prepared her for a career as an outspoken lesbian comedian (Abby Wambach).Cameron Esposito wanted to be a priest and ended up a stand-up comic. Now she would like to tell the whole queer as hell story. Her story. Not the sidebar to a straight person's rebirth-she doesn't give a makeover or plan a wedding or get a couple back together. This isn't a queer tragedy. She doesn't die at the end of this book, having finally decided to kiss the girl. It's the sexy, honest, bumpy, and triumphant dyke's tale her younger, wasn't-allowed-to-watch-Ellen self needed to read. Because there was a long time when she thought she wouldn't make it. Not as a comic, but as a human. SAVE YOURSELF is full of funny and insightful recollections about everything from coming out (at a Catholic college where sexual orientation wasn't in the nondiscrimination policy) to how joining the circus can help you become a better comic (so much nudity) to accepting yourself for who you are-even if you're, say, a bowl cut-sporting, bespectacled, gender-nonconforming child with an eye patch (which Cameron was). Packed with heart, humor, and cringeworthy stories anyone who has gone through puberty, fallen in love, started a career, or had period sex in Rome can relate to, Cameron's memoir is for that timid, fenced-in kid in all of us-and the fearless stand-up yearning to break free.
Keywords: amériques; approches et analyses; corps; humour; identités LGBTQIA2+; personnes lesbiennes; privilèges; régions géographiques; sexisme; sexualité; systèmes d'oppressions; thématiques; travail; états-unis